Thermal-fluid behavior analysis of skin cancer photothermal therapy with variation in intratumoral single blood vessel diameter and velocity - Kim, Donghyuk; Paik, Jeeyong; Kim, Hyunjung (International Journal of Heat and Fluid Flow, 2024)
Recently, usage of nanoparticles, nanometer sized materials, in several therapeutic techniques including photothermal therapy, which uses elevated temperatures to kill tumor tissue, is on the rise. In this study, implementation of photothermal therapy for blood vessels of various diameters, present in the skin layer of squamous cell carcinoma, is simulated using numerical analysis. The optical properties of the nanoparticles were calculated using the discrete dipole approximation method, and the optical properties of the medium were calculated using the optical coefficients calculation method of a composite medium. The calculated optical properties revealed the temperature distribution in the medium using the energy equation, and the flow rate of blood through various vessel diameters using the continuity and momentum equations. Finally, the calculated temperature distribution was used to quantitatively confirm the therapeutic effect of different photothermal treatment conditions through the apoptotic variable. This is expected to serve as a standard for selecting optimal treatment conditions when performing actual photothermal therapy in the future.
Keywords: Blood-flow rates; Gold nanoparticle; Gold Nanoparticles; Optical-; Photothermal therapy; Property; Thermal damage; Thermal fluids; Treatment conditions; Vessel diameter; Apoptosis; Blood flow rate; Blood vessels; Gold nanoparticles; Photothermal therapy; Thermal damage; Vessel diameter